Multi-room conditional access system - GENEVOIS, CHRISTOPHE; QUILLIEN, GUY; LAPERCHE, YANNICK-OLIVIER (2006)
For use in a multi-room conditional access system a conditional access module is provided that incorporates a master smartcard reader and a slave smartcard reader, descrambling means and a multi-room application safely stored inside of the module. The descrambling means for descrambling a data stream requires control words provided by a conditional access application in the module subject to the presence of a valid slave smartcard in the slave smartcard reader, and subject to being enabled by the multi-room application. The multi-room application enables the descrambling means only in presence of a valid master smartcard in the master smartcard reader. Each time the multi-room application enables the slave smartcard, the slave smartcard is enabled only for a limited period of time.